2011
DOI: 10.1159/000323584
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 and Nitric Oxide Levels in Patients with Glaucoma

Abstract: Aims: To investigate the levels of endothelin-1 (ET-1) and nitric oxide (NO) in the aqueous humor and plasma of human eyes with different types of glaucoma: primary open-angle glaucoma (POAG) and chronic closed-angle glaucoma (CCAG). Methods: Patients were classified into 3 groups: group I comprised 35 patients with POAG, group II comprised 25 patients with CCAG, and 30 patients with senile cataract (group III) were used as a control group. Aqueous humor and corresponding plasma were analyzed for ET-1 and NO c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 42 publications
1
33
0
1
Order By: Relevance
“…A number of previous cross-sectional studies have shown that basal levels of plasma (or serum) ET-1 in patients with glaucoma were elevated at a higher level than control subjects. [12][13][14] Conversely, other studies showed no significant difference in plasma (or serum) ET-1 between subjects with glaucoma patients and normal control subjects [54][55][56][57] or lower levels of plasma ET-1 in patients with glaucoma when compared with normal subjects. 15 Although the conflicting conclusions indicate that no consensus regarding plasma (or serum) levels of ET-1 in patients with glaucoma have been reached, it is possible that data from all studies are accurate, since plasma (or serum) ET-1 levels may fluctuate due to seasonal, circadian, and other factors.…”
Section: Discussionmentioning
confidence: 87%
“…A number of previous cross-sectional studies have shown that basal levels of plasma (or serum) ET-1 in patients with glaucoma were elevated at a higher level than control subjects. [12][13][14] Conversely, other studies showed no significant difference in plasma (or serum) ET-1 between subjects with glaucoma patients and normal control subjects [54][55][56][57] or lower levels of plasma ET-1 in patients with glaucoma when compared with normal subjects. 15 Although the conflicting conclusions indicate that no consensus regarding plasma (or serum) levels of ET-1 in patients with glaucoma have been reached, it is possible that data from all studies are accurate, since plasma (or serum) ET-1 levels may fluctuate due to seasonal, circadian, and other factors.…”
Section: Discussionmentioning
confidence: 87%
“…6,7 Additional research in this area has focused on humoral abnormalities in patients with OAG. A number of molecules are currently under investigation, such as endothelin-1, 8 vascular endothelial growth factor, 9 tumor necrosis factor-alpha, 10 matrix metalloproteinases, and their inhibitors. 11 Lipocalin-like prostaglandin D synthase (L-PGDS, also called b-trace protein) is a mainly brain-derived protein with a molecular mass of 28 kD.…”
mentioning
confidence: 99%
“…Undiluted AH samples out of the AC were harvested at the start of each procedure immediately after preparation of the first paracentesis. This course of action was described as safe in former studies [8,9] . Preoperatively, ACD and axial length were measured with a Zeiss IOL-Master in 102 eyes (95%) and with an Alcon UltraScan in 5 eyes (5%) due to dense opacities of the lens.…”
Section: Patientsmentioning
confidence: 76%
“…Different surgeons with different techniques [2,4,6,8] have performed AH collections out of the AC in conjunction with various types of anterior segment surgery, including cataract removal via phacoemulsification or trabeculectomy [9] in the past. Furthermore, diagnostic paracentesis was performed especially in uveitis patients [8] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation